Using an Interactive Video Simulator to Improve Certified Nursing Assistants' Dressing Assistance and Nursing Home Residents' Dressing Performance: A Pilot Study. Issue 4 (April 2018) - Tsai, Pao-Feng; Kitch, Stephanie; Beck, Cornelia; Jakobs, Thomas; Rettiganti, Mallikarjuna; Jordan, Kerry; Jakobs, Erik; Adair, Shawn
Abstract : This pilot study examined the initial effects and estimated effect size of a computer-based simulation education program on certified nursing assistants' level of assistance when dressing nursing home residents with dementia and on residents' dressing performance. Nine dyads, assigned to either the experimental or control group, completed the study. Both groups received a traditional 1-hour education module delivered by a research assistant. The experimental group was then instructed to undertake an additional 2-hour intervention using a video simulator that enabled nursing assistants to practice level of assistance skills. The appropriateness of dressing assistance from nursing assistants and residents' dressing performance was measured before and 6 weeks after the intervention. The results showed that the two groups did not significantly differ in either appropriate levels of dressing assistance ( P = .42) or residents' dressing performance ( P = .38). A lack of effort by some assistants to properly assist residents and low statistical power may explain the lack of significance. The effect sizes of the experimental intervention on appropriate levels of dressing assistance and resident dressing performance were 0.69 and 0.89, respectively. Incorporating a strategy to improve motivation should be considered in future studies.